Rabbit production in Nigeria: some aspects of current status and promotional strategies (1999)
Some aspects of the current status and promotional strategies of rabbit production in Nigeria were appraised in this study. This was because such data are lacking and rabbit production offers a great potential towards attainment of food security in terms of animal protein intake. Data were obtained principally from field survey, questionnaires administration, personal observations and experiences of authors, structured personal interviews of identified rabbit farmers, personal interview and observational data from agricultural extension agents, personal interview and visitation to markets and retail outlets for rabbit, proxy information from distant collaborators, recorded data from Government establishments and published data. All the information collected was synthesized to provide an informative blend on major aspects of rabbit production. From the data collected, it was found that rabbit production in Nigeria is largely a traditional, non-commercially oriented, family-consumption targeted, and smallholder type operation comprising an average of 2-7 does and 3 bucks. About 3.4-5.2% of the Nigerian population may be keeping rabbits with women and children being mostly involved. Rabbit keeping is both intensive and semi- intensive, though some scattered free range backyard rearing was recorded. Unlike the rural rabbit keepers, space is limiting for most urban rabbit keepers. Diets of rabbits in Nigeria are primarily forages, grasses and legumes, kitchen wastes while commercial feeds are rarely fed. Bucks and does are under-utilized, with does producing about 20 weaned rabbit per year and are usually offered for sale after four parities. Nigerian rabbits do not suffer any peculiar disease, however skin disease (mange) and coccidia infection are very common. There are high peri- and post-natal mortalities, and it was estimated that overall mortality between birth and marketing was between 30-40%, being highest in the young ones. The performance and reproductive productivity of rabbits in Nigeria are strongly correlated with the level of management. There exists a latent and growing market for rabbit meat in Nigeria especially as an alternative livestock species. We propose promotional strategies for sustainable rabbit production.